Structural characterization, thermal, ac conductivity and dielectric properties of (C7H12N2)2[SnCl6]Cl2·1.5H2O. (3rd May 2016) - Hajji, Rachid; Oueslati, Abderrazek; Hajlaoui, Fadhel; Bulou, Alain; Hlel, Faouzi
Abstract : (C7 H12 N2 )2 [SnCl6 ]Cl2 ·1.5H2 O is crystallized at room temperature in the monoclinic system (space group P21 /n). The isolated molecules form organic and inorganic layers parallel to the (a, b) plane and alternate along the c -axis. The inorganic layer is built up by isolated SnCl6 octahedrons. Besides, the organic layer is formed by 2, 4-diammonium toluene cations, between which the spaces are filled with free Cl − ions and water molecules. The crystal packing is governed by means of the ionic N—H··· Cl and Ow—H··· Cl hydrogen bonds, forming a three-dimensional network. The thermal study of this compound is reported, revealing two phase transitions around 360(±3) and 412(±3) K. The electrical and dielectric measurements were reported, confirming the transition temperatures detected in the differential scanning calorimetry (DSC). The frequency dependence of ac conductivity at different temperatures indicates that the correlated barrier hopping (CBH) model is the probable mechanism for the ac conduction behavior.